The Effect of Anti-Tuberculosis Drugs on the Effectiveness of Anti-Retroviral Therapy in HIV-AIDS Patients - Hasriana, Hasriana; Alfian, Sofa D.; Milanda, Tiana; Abdulah, Rizky (Pharmacology and Clinical Pharmacy Research)
patients who infected by Humman Immunodeficiency Virus (HIV) in developing countries. The purpose of this study was to determine the effect of anti-tuberculosis drugs (ATB) on the effectiveness of anti-retroviral (ARV) therapy in HIVâAIDS infected patients.This study was a prospective cohort study conducted at outpatient clinic of Abepura Hospital during April-June 2015. The data were taken from medical records, which include CD4 level, gender, age, education and stage of disease. Statistical analysis was performed using bivariate and multiple regression analysis. A total of 28 subjects was included in this study (7 HIV patients and 21 TB-HIV patients). The results of bivariate analysis showed that there was no significant difference on general characteristics of patients using ARV-ATB and without ATB. Gender, age, occupation, education and the stage of disease did not affect the value of CD4 patients (p>0.005). The result from paired t-test showed that there was no significant difference in the level of CD4 cell, before and after treatment using ARV (pË0.912), while therapy with ARV-ATB showed significant differences (pË0.002). In conclusion, this study showed that the combination of ATB and ARV could increase CD4 level up to 72%. Thus, the use of ATB drugs on ARV patients who infected by TB is recommended to reduce disease burden.Keywords: anti-retroviral therapy , HIV- AIDS, tuberculosis